2004
DOI: 10.1016/j.orthres.2003.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Internodes can nearly double in length with gradual elongation of the adult rat sciatic nerve

Abstract: Leg lengthening procedure is used increasingly to treat leg length discrepancy and some forms of dwarfism. We investigated adaptation in rat sciatic nerve to the gradual nerve elongation that occurs with leg lengthening. Indirect nerve elongation was produced by leg lengthening by a total of 15, 30, 45, or 70 mm at a rate of 1 m d d a y . One day after leg lengthening completion, transverse semithin sections of sciatic nerve were prepared and examined; a teased-fiber study also was performed. Elongation decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 28 publications
(38 reference statements)
1
34
0
1
Order By: Relevance
“…The ability of mitochondria to reorganize is crucial in maintaining a uniform density given the factors that lead to gradients in distribution. Namely, axons are viscoelastic structures which can be deformed either by growth cone induced stretching or towed growth of pre-synaptic (Dennerll et al, 1989) or mature neurons (Abe et al, 2004;Pfister et al, 2004), and mitochondria eventually become depolarized and are transported back to the cell body (Miller and Sheetz, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability of mitochondria to reorganize is crucial in maintaining a uniform density given the factors that lead to gradients in distribution. Namely, axons are viscoelastic structures which can be deformed either by growth cone induced stretching or towed growth of pre-synaptic (Dennerll et al, 1989) or mature neurons (Abe et al, 2004;Pfister et al, 2004), and mitochondria eventually become depolarized and are transported back to the cell body (Miller and Sheetz, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…As neurons constantly generate tension that minimizes axonal length both before and after synapse formation (Van Essen, 1997), it follows that increases in the length of the axon are the result of forces generated by an increase in body size. Consistent with the view that neurons respond to forced lengthening by increasing the production of new material are studies that have shown that axons are able to maintain viability and increase their caliber when artificially stretched to remarkable lengths (Abe et al, 2004;Pfister et al, 2004Pfister et al, , 2006. For these reasons it would be useful to have a model where influx is allowed to vary over the course of elongation.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…lengthening. Our previous study has shown that changes of deterioration have not been seen in femoral lengthening in rats at 1 mm/day [16].…”
Section: Discussionmentioning
confidence: 85%
“…33,34 Intriguingly, the maximum strain at which this straightening occurs is just above 8%, the same threshold at which reversible conduction blocks are initiated. 31,35 Second, nerve lengthening has been reported to irreversibly elongate nodes of Ranvier, 32,33,36,37 which by virtue of their small caliber, are particularly susceptible to mechanical loads. Secondary effects of ischemia to compromised blood flow have also been reported, 30,38 but do not likely induce short-term deficits in electrophysiological or morphological properties.…”
Section: Biomechanics Of the Peripheral Nervous Systemmentioning
confidence: 99%